2007
DOI: 10.1080/02732170701534242
|View full text |Cite
|
Sign up to set email alerts
|

The Fema Trailer Parks: Negative Perceptions and the Social Structure of Avoidance

Abstract: In recent years, negative media attention has fostered the impression that Federal Emergency Management Agency (FEMA) parks are social wastelands filled with criminal elements and other undesirables. FEMA parks have subsequently come to be viewed by some as a major threat to the safety and quality of life of the local communities in which they are situated. This analysis addresses attitudes toward FEMA trailer parks in Baton Rouge after Hurricane Katrina among Baton Rouge residents. Drawing on the Locally Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Whether residents from the local area themselves were placed in these trailer parks may have made a difference in levels of acceptance from the neighborhood (cf. Lee, Weil, and Shihadeh ). Unfortunately, these data are more difficult to collect because of privacy concerns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether residents from the local area themselves were placed in these trailer parks may have made a difference in levels of acceptance from the neighborhood (cf. Lee, Weil, and Shihadeh ). Unfortunately, these data are more difficult to collect because of privacy concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Large‐scale surveys of Southern residents after Katrina confirmed the negative views that most citizens have of such facilities. In interviews with more than 1,000 local residents in East Baton Rouge Parish (located close to the city of New Orleans), Lee, Weil, and Shihadeh (, 752) found that more than half of the respondents envisioned trailers parks as bringing trash and litter, increasing crime, and driving property values down. Logistic regression models show that white respondents were particularly sensitive to the issues of trash, litter, and crime and would be more likely to engage in “avoidance behaviors” such as changing their driving routes to avoid contact or, if necessary, going so far as to sell their homes.…”
Section: Trailers As Controversial Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates a high level of organizing ability and positions them as influential voters in New Orleans. Lee citing Aldrich writes, "the dark side of community social capital was revealed when the communities with a more vibrant civic culture or with more political power were more effective at retarding FEMA trailer placements than those with less social capital" (Lee, 2007). Lakewood is a perfect example of this dark side.…”
Section: Communication Social Capital and Common Denominatorsmentioning
confidence: 99%